Evaluation of the Land Cover Changes in Mosul City, Iraq, Using Remote Sensing and GIS - Karam, Noor Z.; Ahmed, Bushra A. (Iraqi Journal of Science, 2026)
Remote sensing techniques have been utilized to assess and manage natural resources in general and vegetation, in particular, to preserve the sustainability of plant wealth, evaluate and explain the current state of the vegetation condition, and determine the changes that occur to it as a result. Mosul’s forests are exposed to many fires, including in 2017, 2021, and 2022. This study used Landsat8 satellite images and Geographic Information Systems (GIS). Some spectral indices were used, such as the Normalized Difference Vegetation Index (NDVI), Soil Adjusted Vegetation Index (SAVI), and Enhanced Vegetation Index 2 (EVI2). Land Surface Temperature (LST) was also calculated, in addition to the Normalized Difference Built-up Index (NDBI) and Normalized Difference Water Index (NDWI). LST was used to evaluate the extent to which plants are affected by the land surface temperature in Mosul city. According to the rate for the three years, the EVI2 index for the fourth month of 2023 had the highest vegetation, at 21.70%, while the NDVI index for the sixth month of 2015 had the lowest percentage. This study discovered that temperatures and fire clarity affect the vegetation cover rate, noting that the areas that have decreased and changed the most were those exposed to fires in 2017 and 2022.